The Analysis of the Essence on the Information Society in the Legal and Philosophical Context - Kostytsky, Mychailo V.; Kushakova-Kostytska, Nataliia V.; Serdiuk, Ivan V.; Gvozdik, Oleg I. I.; Pavlyshyn, Oleg V. (Cuestiones Políticas, 2020)
This article analyzes the main conceptual approaches to understand a new type of information society. The methodology used in terms of intellectual operations to process information combined the dialectical method, historical method, comparative method, systemic and functional method, formal and logical method. The formation of the information society is the result of the new global social revolution that is based on the explosive nature of development and the convergence of information and communication technologies. It is a knowledge society, where the main condition for the well-being of each person and each state is the knowledge acquired due to free access and the ability to work with information. By way of conclusion, everything indicates that the main value of the information society is the formation of open access information spaces that improve the quality of life and human capacities, and promote the development of open societies.